Mid- to long-term complications and revision rates of robotic-assisted unicompartmental knee arthroplasty: a systematic review and meta-analysis - Chen, Xiaolin; Wang, Bowen; Huang, Jianming; Huang, Zheyuan; Weng, Weizong; Huang, Danlei; Xie, Desheng; Zhang, Ying (Frontiers in Surgery, 2025)
ObjectiveUnicompartmental knee arthroplasty (UKA) is a commonly performed procedure for patients with isolated osteoarthritis (OA). In recent years, robotic-assisted UKA (RAUKA) has raised concerns regarding its revision rates and risk of complications. This study aims to compare the mid- to long-term complications and revision rates between RAUKA and traditional UKA, providing evidence to support its clinical application.MethodsIn accordance with PRISMA guidelines, we conducted a systematic review of studies comparing complication and revision rates between RAUKA and traditional UKA, with a minimum average follow-up duration of three years. Comprehensive searches were conducted in PubMed, Embase, Web of Science, and Cochrane databases, with a cutoff date of October 1, 2024. The outcome measures analyzed included complications, revision rate, postoperative aseptic loosening, fractures, malalignment, pain, and OA.ResultsSix studies were included, encompassing 48,091 knee cases, with follow-up durations ranging from 36–106.4 months. RAUKA significantly reduced the overall complication rate (odds ratio: 0.27, 95% CI: 0.11–0.63, P = 0.003) and revision rate (odds ratio: 0.28, 95% CI: 0.12–0.67, P = 0.004) compared to traditional UKA. RAUKA also significantly reduced the incidence of postoperative aseptic loosening (odds ratio: 0.29, 95% CI: 0.17–0.50, P < 0.001) and fractures (odds ratio: 0.20, 95% CI: 0.05–0.79, P = 0.020). However, no significant differences were found between the two groups for postoperative malalignment, pain, or secondary OA.ConclusionsThis study is the first to include mid- to long-term follow-up (≥3 years) data comparing RAUKA and traditional UKA. The findings indicate that RAUKA outperforms traditional UKA in terms of overall complication and revision rates, with a lower incidence of key complications such as postoperative aseptic loosening and fractures. RAUKA appears to be a safer surgical option for OA patients, supporting its broader clinical application. However, further long-term, multicenter studies are needed to fully validate its efficacy and long-term safety.Systematic Review Registrationidentifier [ID CRD42024605539].